Late-Victorian Gentlemen Entrepreneurs Venturing Into New Worlds of Canadian Business: The Nestegg Mining Company, 1896-98 - Chapin, Patrick (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2005)
AbstractThis case study examines how a group of late nineteenth century Victoria businessmen adjusted to the transition from traditional family capitalism to joint stock company management of a remote speculative mining venture. They encountered numerous unfamiliar obstacles including prejudicial management, the long-distance factor, public investors, and innovations in advertising and financing. Ultimately, Victoria’s unique geography and cultural setting foiled their efforts to establish themselves as Western Canada’s centre of venture capitalism.